Determination of lead, cadmium and nickel from paint chips using atomic absorption spectrophotometry with chemometrics for forensic investigation - Mahmood, Mazuin Che (2022)
Paint is an important forensic evidence found at crime scene, especially in vehicular related incidents. Through detailed examination, such evidence could aid in linking people, places, and an object where the paint sample originated from. Routinely, the forensic comparison is conducted to observe the similarities and differences in appearance, layer sequence, size, shape, thickness, or some physical or chemical characteristics of the two paint samples in question and reference. However, reference samples might not be available on all occasions; therefore, efforts shall be initiated to generate more information on the profiles of paint samples to provide forensic investigative clues. This study aimed to determine the contents of lead (Pb), cadmium (Cd) and nickel (Ni) in the paint chip samples using Flame Atomic Absorption Spectrophotometry (FAAS) followed by clustering and/or discrimination through chemometrics. In this study, a total of 65 paint samples were collected from various sources. These samples were accurately weighed and subjected to an acid digestion procedure using a combination of nitric acid and hydrogen peroxide. All the digested samples were then analysed using FAAS. It was found that most paint samples tested in this study were detected with the presence of the three target elements, except 14 samples for Pb, 8 samples for Cd, and only two samples of Ni. Decomposition of the elemental profiles by principal component analysis (PCA) allowed for discrimination of certain paint samples from the main cluster, suggesting their differences in the contents of Pb, Cd, and Ni. To conclude, the application of FAAS enabled the determination of the Pb, Cd and Ni in the paint samples and PCA allowed for discrimination, where such evidence shall be analysed for their elemental profiles to assist the forensic investigation.